PROTECTIVE EFFECTS OF ETHANOLIC EXTRACT OF PSIDIUM GUAJAVA ON ADRIAMYCIN-INDUCED NEPHROTOXICITY AND GENOTOXICITY IN RATS (2013)
Adriamycin, a widely used anti-cancer drug, induces nephrotoxicity and genotoxicity in experimental animals through generation of free radicals. Phenolic phytochemicals in guava leaves possess antioxidant properties. Hence, they could play a protective role in adriamycininduced nephrotoxicity and genotoxicity. The protective effects of Ethanolic Extract of Psidium guajava (EEPG) on adriamycin-induced nephrotoxicity and genotoxicity were investigated in rats. Dried powdered guava leaves (2kg) were extracted with ethanol and concentrated in rotary evaporator to obtain the EEPG. Two hundred male Wistar rats (weighing180g-220g) were divided into control, adriamycin-treated (single dose-20mg/kg and cumulative dose-15mg/kg, i.p), and adriamycin and EEPG-treated (125, 250 and 500mg/kg p.o) animals in pre-, and cotreatments. Genotoxicity test involved bone marrow cytology to identify Micronucleated Polychromatophilic Erythrocytes (MPEs) 24 hrs after treatments. Animals were sacrificed by cervical dislocation and blood was obtained to determine blood urea nitrogen and creatinine. Post-mitochondrial fraction of kidney homogenate was used to evaluate Lipid Peroxidation (LPO), Cytochrome P450 3A4 (CYP3A4), antioxidant enzymes [Superoxide Dismutase (SOD), catalase, glutathione-S-transferase, Glutathione Peroxidase (GPx), Glutathione Reductase (GR)] activities, and glutathione level spectrophotometrically. Antioxidant activity of EEPG was assessed in vitro using 2-2-Azobis-2´ Amidinopropane-Hydrochloride (AAPH)-induced LPO model and Radical Scavenging Activities (RSA) against hydrogen peroxide (H2O2), hydroxyl, nitric oxide and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals were determined spectrophotometrically. Histological changes in the kidney were assessed using a light microscope. The EEPG was fractionated by column chromatography over silica gel and sephadex LH-20 and its purified compound analysed for chemical structure by infrared and nuclear magnetic resonance spectroscopy. Data were analysed using ANOVA and Student’s t-test at p=0.05. About 500g of EEPG was obtained from 2kg of leaves. Renal dysfunction caused by 20mg/kg adriamycin (urea,-7.6μmol/L, creatinine,-11.8μmol/L) was prevented by pre-treatment with EEPG at 250mg/kg (4.9μmol/L, 7.9μmol/L) while antioxidant status was improved significantly by reducing LPO (0.5nmol) and increasing activities of SOD (3.6units), GPx (0.3nmol), catalase (0.1μmol), glutathione-S-transferase (0.3nmol), GR (0.6nmol) and glutathione level (16.0μg/g) when compared with adriamycin-treated rats (0.9nmol, 1.7units, 0.1nmol, 0.04μmol, 0.2nmol, 0.4nmol and 13.9μg/g), respectively. Increase in creatinine by 15mg/kg adriamycin (1.0mg/dL) was reduced by co-treatment with 250 and 500mg/kg EEPG (0.4mg/L, 0.3mg/dL). This reduction was accompanied by increase in glutathione-S-transferase activity (0.11nmol, 0.09nmol) when compared with adriamycin (0.08nmol) and inhibition of CYP3A4 activity (7.9±0.3, 8.2±0.2) when compared with adriamycin (9.0±0.1). Toxicity was profound when adriamycin was administered as cumulative dose. The EEPG (125, 250 and 500mg/kg) decreased the frequency of MPE (11.8, 8.8 and 3.4/1000 MPEs respectively) when compared with 20mg/kg adriamycin (19.3/1000 MPEs). The EEPG showed significant antioxidant activities in vitro through reduction of AAPH-induced LPO-65.3%, RSA in H2O2- 98.7%, nitric oxide-30.1%, DPPH.-70.4% and hydroxyl radicals-72.8% when compared with catechin (39.5%, 62.8%, 32.2%, 44.9% and 55.5%) respectively. Adriamycin induced renal tubular necrosis, while normal renal histology was maintained with EEPG at all doses. The purified compound from EEPG was found to be a triterpene. Ethanolic extract of Psidium guajava protected rats against adriamycin-induced nephrotoxicity and genotoxicity. Free radical scavenging property and antioxidant activity of ethanolic extract of Psidium guajava may be responsible for this protective effect.